Improved Synthetic Method for 5-[(Phenylthio)methyl]oxazoline Derivatives: Electrophilic Cyclization of Allylic Amide Using a Brønsted Acid and Tetrabutylammonium Chloride under Mild Conditions - Nagao, Yoshihiro; Hiroya, Kou (Synlett, 2020)
The synthesis of oxazolines using electrophilic cyclization of allylic amide is a simple and powerful method. However, cyclization involving arylsulfenylation requires harsh reaction conditions. We found that the reaction proceeds under mild heating conditions with the combination of a Brønsted acid and tetrabutylammonium chloride. This method enabled the synthesis of 5-[(arylsulfenyl)methyl]oxazoline derivatives under mild conditions and demonstrated high tolerance for various functional groups.
Keywords: oxazoline; oxazine; thioether; sulfide; electrophilic cyclization